2021
DOI: 10.2147/ccide.s316838
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Plaque Control in Peri-Implant Mucositis Initiation as Opposed to the Role of Systemic Health Condition: A Cross-Sectional Study

Abstract: Purpose The aim of this study was to investigate the priority of periodontal plaque as a risk factor compared to other risk factors, namely hypertension and diabetes mellitus type II, regarding the initiation and severity of peri-implant mucositis, eventually reinforcing the importance of plaque control, periodic maintenance and supportive periodontic treatment after implant placement in order to prevent peri-implant diseases. Patients and Methods A total of 58 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 49 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Patients with hypertension are more likely to experience attachment loss and severe gingivitis because of a heightened immunological response. In patients with hypertension and those with coronary heart disease, inflammatory mediators like interleukins, c‐reactive proteins, tumour necrosis factor and metalloprotease are released, leading to a triggered immune response 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with hypertension are more likely to experience attachment loss and severe gingivitis because of a heightened immunological response. In patients with hypertension and those with coronary heart disease, inflammatory mediators like interleukins, c‐reactive proteins, tumour necrosis factor and metalloprotease are released, leading to a triggered immune response 24 …”
Section: Discussionmentioning
confidence: 99%
“…In patients with hypertension and those with coronary heart disease, inflammatory mediators like interleukins, c-reactive proteins, tumour necrosis factor and metalloprotease are released, leading to a triggered immune response. 24 In general, antihypertensive prescriptions help in bone generation and a lesser risk of bone fractures. 25 According to a study by Seki et al, antihypertensive medicines adversely affect dental implants.…”
Section: /455mentioning
confidence: 99%
“…In all, 51 studies were identified concerning the influence of prediabetes and diabetes mellitus type I or II on the onset of late complications in dental implants: 14 were prospective [15][16][17][18][19][20][21][22][23][24][25][26][27][28]; 23 retrospective ; 10 cross-sectional [52][53][54][55][56][57][58][59][60][61] and 5 of unspecified design [62][63][64][65][66]. Thirty-three of these studies found no association between the success or failure of dental implants and diabetes, while seventeen reported a positive correlation, and in one (cross-sectional) study the peri-implant inflammation parameters were better in patients with diabetes and hypertension than in healthy individuals [53] Articles were grouped by findings concerning diabetes as a risk factor for biological complications of dental implants (Table 1). Four of the fifty-one studies [31,52,58,59] identified prediabetes as a risk factor for periimplant inflammation.…”
Section: Diabetes and Prediabetesmentioning
confidence: 99%
“…The seven studies identified (four retrospective and three cross-sectional) were almost unanimous in finding no evidence of hypertension being a risk factor for dental implant rehabilitation [44,46,47,53,54,57]. The only exception was one study reporting a higher rate of implant failure in hypertensive patients [48].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation